Surgical revascularization of the myocardium by minimally invasive access - Conde Moncada, Roger Yoel (2023)
Median sternotomy is the Gold Standard access for surgical revascularization of the myocardium, but it is not free of complications, especially in patients with multiple comorbidities. Minimally invasive access offers the advantage of avoiding sternotomy, achieving a more accelerated postoperative recovery, with less hospital stay time and a higher level of satisfaction with quality of life. We present the case of a 49-year-old male patient, diabetic, hypertensive, smoker, with multiarterial coronary artery disease, very symptomatic, who underwent surgical revascularization by left mini-thoracotomy.